2014
DOI: 10.1080/09593330.2014.952342
|View full text |Cite
|
Sign up to set email alerts
|

Flue-gas-influenced heavy metal bioaccumulation by the indigenous microalgaeDesmodesmus communisLUCC 002

Abstract: Desmodesmus communis LUCC 002 was cultivated using flue gas originating from a coal-fired power plant as a carbon dioxide (CO2) source. The flue gas contains various heavy metals. For investigating the fate of flue-gas-introduced metals on the cultivation system, bioaccumulation was measured in the microalgal biomass and milieu. The accumulated biomass was found to contain eight heavy metals: arsenic, chromium, barium, lead, selenium, silver, cadmium, and mercury. High heavy metal accumulations were also found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Batch cultures provide the simplest form of bioreactor operation. They can be used in a variety of different applications, for instance to make microbial products that can be used to mitigate carbon dioxide or to provide a source of biofuel. Palanisami and his co-workers reported that the most common microalgae found in soil and freshwater are of the genera Desmodesmus and Scenedesmus . Their investigation of the species ( Desmodesmus communis ) revealed that these algae were not only able to tolerate the toxic chemicals in flue gas but grew well.…”
Section: Introductionmentioning
confidence: 99%
“…Batch cultures provide the simplest form of bioreactor operation. They can be used in a variety of different applications, for instance to make microbial products that can be used to mitigate carbon dioxide or to provide a source of biofuel. Palanisami and his co-workers reported that the most common microalgae found in soil and freshwater are of the genera Desmodesmus and Scenedesmus . Their investigation of the species ( Desmodesmus communis ) revealed that these algae were not only able to tolerate the toxic chemicals in flue gas but grew well.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide shortage of fossil fuels is an urgent problem. It enforces scientists to accelerate the search for alternative fuels (Vicente et al, 2004).The bio-fuel production from photosynthetic microorganisms is considered as a process to produce renewable energy for global warming mitigation (Palanisami et al, 2013). In recent times microalgae have received much attention as a renewable energy resource (Hsieh and Wu, 2009).…”
Section: Introductionmentioning
confidence: 99%